Rathke's cleft cyst - Ringel, Steven P. (1972)
A 29 year old female with a chiasmal syndrome secondary to a Rathke's cleft cyst is described. The histology and pathogenesis of these rare cysts are discussed, contrasting them with other hypophysial cysts.